Agrarian reform and problems of local self-government in Russia in the early twentieth century - N. D. Sudavtsov (Современная наука и инновации)
The article deals with the problems of local self-government in rural areas during the agrarian reform in Russia after the First Russian revolution (1905-1907), as well as its impact on the development of agriculture. The positions of the government and society on this problem, the attitude of the State Duma and the State Council to it are considered.